The Influence of Makan Bajamba on the Social Behavior of Children Aged 5–6 Years - Indriani , Faradila; Marlina, Serli; Yeni, Indra; Sari, Resti Elma (UNIB Press, 2025)
Social behaviour in early childhood is a crucial foundation in the development of character and interpersonal competence from an early age through eating bajamba. This study aims to evaluate the impact of eating bajamba activities on the social behaviour of 5-6-year-old children at Sabbihisma 2 Ulak Karang Kindergarten. This research applied quantitative methodology with a quasi-experimental design. The research participants included 20 children classified into two groups, namely 10 children from class B3 as the treatment group and 10 children from class B4 as the control group, which were determined through a purposive sampling method. The research measurement tool was a test instrument containing nine statement items to assess children's social behaviour. The data analysis process was carried out using the SPSS version 25.0 application, starting with normality and homogeneity testing, which proved that the data were normally distributed and had uniform variance. Then, the independent sample t-test was implemented, which resulted in a probability value (2-tailed) of 0.014 < 0.05 and a calculated t value of 2.730 > t table of 1.734. The output indicates that the bajamba eating activity has a significant effect on improving children's social behaviour. The results of this study are expected to serve as a reference in the formulation of a more dynamic and engaging learning approach to support the construction of early childhood social character